Effects of Combined Heat and Preservative Treatment on Storability of Ponkan Fruit (Citrus reticulata Blanco cv. Ponkan) during Postharvest Storage - Dandan Tang; Qiong Lin; Juanying Lin; Dengliang Wang; Chunrong Liu; Wenming Wu; Chongde Sun; Kunsong Chen (Journal of Food Quality)
Heat treatment and preservative application have been widely used during postharvest storage of many fresh products, but the effect of their combination on citrus storage has rarely been investigated. In this study, the optimal heat treatment (HT) conditions and HT combined with preservative treatment were investigated for Ponkan fruit (Citrus reticulata Blanco cv. Ponkan) storage. Results indicated that HT at 55°C for 20 s can significantly reduce the decay rate of Ponkan fruit, and a combination of HT and 25% of the preservative dosage used in production of iminoctadine tris (albesilate), 2,4-dichlorophenoxyacetic acid, and imazalil significantly reduced the decay rate without affecting fruit quality. In addition, the increased fiber contents in fruit receiving the HT combined with preservative treatments may be a response preventing fungus infection and enhancing fruit storability and resistance. The above results suggested that the combination of HT and 25% of the preservative production dosage was optimal for controlling Ponkan fruit decay during storage.